2015
DOI: 10.1080/02786826.2015.1123214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and pressure on carbon black size distribution during allothermal cracking of methane

Abstract: Allothermal cracking of methane is a suitable and eco-friendly way to simultaneously produce hydrogen and carbon black. The economic viability of the process relies on the ability to produce carbon black having well-defined characteristics, particularly concerning the particle size. A model for the study of the carbon particle size distribution during thermal cracking of methane has been developed. The model takes into account: heat transfer by conduction, convection, particle and gas radiation, homogenous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thermal plasma is considered a major energy efficient technology for tunable high temperature heat sources, especially when paired with renewable energy sources substituting conventional furnaces that operate on thermoelectric energy sources. CB has been produced from the thermal plasma of methane and polymers, and long studied and modeled pilot processes are now becoming commercially available [75][76][77][78][79][80][81]. Converting carbon-based feeds without combustion for energy input has the benefit to drastically reduce CO 2 emissions.…”
Section: Alternative Production Methodsmentioning
confidence: 99%
“…Thermal plasma is considered a major energy efficient technology for tunable high temperature heat sources, especially when paired with renewable energy sources substituting conventional furnaces that operate on thermoelectric energy sources. CB has been produced from the thermal plasma of methane and polymers, and long studied and modeled pilot processes are now becoming commercially available [75][76][77][78][79][80][81]. Converting carbon-based feeds without combustion for energy input has the benefit to drastically reduce CO 2 emissions.…”
Section: Alternative Production Methodsmentioning
confidence: 99%
“…The available experimental data do not give us enough evidence for a detailed comment on the atomic structure of the carbon nanoclusters. They could be heavy C n H z species formed in the cooler outer regions of plasma [46][47][48], or solid carbon particles [49,50] which are not thermally desorbed or etched by atomic hydrogen. Alternatively, these carbon nanoclusters could be nanoscopic regions of non-diamond formations on the diamond surface.…”
Section: Carbon Nanoclustersmentioning
confidence: 99%
“…It is reported that the color grade of CVD diamond improves with the increase in the flow rate of growth gas in CVD reactor [46,47]. If the carbon nanoclusters are formed in plasma, then one might expect their concentration and size to depend on the gas residence time in the reactor chamber [50]. The faster flow of gas, the smaller size of solid carbon nanoclusters and the lesser their concentration at the diamond surface.…”
Section: Carbon Nanoclustersmentioning
confidence: 99%
“…However, higher energy electrons can cause further dehydrogenation of the methyl radical, as shown in Eqs. (15)- (17). Under these temperature conditions, acetylene is mainly produced from the paths shown in Eqs.…”
Section: Methane Activationmentioning
confidence: 97%
“…High temperature chemistry of methane conversion can be found in publications from Dr. Laurent Fulcheri and his coworkers [17][18][19]. The effect of temperature and pressure on thermal cracking and formation of monodispersed carbon black particle has been addressed.…”
Section: Introductionmentioning
confidence: 99%